Modeling of transient characteristics of an air source heat pump with vapor injection during reverse-cycle defrosting. (April 2018) - Qiao, Hongtao; Aute, Vikrant; Radermacher, Reinhard
Highlights: Dynamic responses of an FTVI heat pump during RCD are modeled. A five-stage hot-gas defrost model is developed. Smooth transition between different defrosting stages is guaranteed. The same system model can simulate both heating and cooling mode. Predicted defrosting efficiency is consistent with published experimental data. Abstract: A thorough literature review indicates that there is a dearth of modeling studies on the defrosting dynamics of air source heat pumps (ASHPs) due to the complex underlying physics and numerous computation details. In an effort to bridge the research gap, this paper first presents a five-stage hot-gas defrost model which is incorporated into a distributed-parameter heat exchange model integrated with a detailed frost growth model proposed in Qiao et al. (2017). Numerical treatments are then proposed to smooth the discontinuous transition between different defrosting stages, resulting in a significant improvement in numerical robustness. The developed models and the component models described in Qiao et al. (2015a) are applied to construct the system model of an air source flash tank vapor injection (FTVI) heat pump. A dynamic simulation is conducted to explore the transient fluid flow and heat transfer phenomena of the system during the reverse-cycle defrosting (RCD). A detailed description of the resulting physical processes is provided. The simulation results indicate that the energy used to melt the frost accounts for 17.7% of the total energy supply from the refrigerant flow, which is consistent with published experimental data for the efficiency of a typical defrosting process.